Goenawan Mohamad [Indonesia, Editor of Tempo] - Mohamad, Goenawan (Institutional Knowledge at Singapore Management University, 2014)
Goenawan Mohamad is the founder of Indonesia's Tempo magazine and a leading voice of democracy in the country. As founding editor, Mr Goenawan had to make the tough call of whether to continue Tempo's critical reporting of the government and face a ban, or toe the line to ensure survival. DNA talks to him about how he came to his decision and stuck to his principles, as well as his take on the many Indonesian leaders he has observed.